Examining the Structural Relationships of Destination Image towards Travel Intention to the Puncak Tourist Area: Mediating role of Perceived Risk, Destination Attractiveness and Perceived Value - Nursiana, Adinoto; Sugiarto, Sugiarto; Kiswantoro, Amin; Hikmawati, Meiana Maulida; Budhijono, Fongnawati; Wahjudi, Januar; Sutrisno, Sutrisno (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2024)
Purpose: This research was conducted with the aim of determining whether tourist’s perception related to destination image which is mediated by perceived risk, destination attractiveness, and perceived value will affect the intention of tourists to visit Puncak Tourism Area.Research Methods: This research was conducted in Jakarta by distributing questionnaires to prospective tourists who had plans to travel to the Puncak Tourism Area. Data were collected using purposive sampling techniques. Data analysis was performed using Structural Equation Modeling with Lisrel 8.80.Results and Discussions: At the 0.05 significance level, empirical data shows that directly destination image has a positive but insignificant effect on the intention to travel. Indirectly the influence of destination image through the mediating variable Perceived Value and through the mediating variable Destination Attractiveness on the intention to travel are also not significant.Conclusion: Only through the mediating variable Perceived risk on the Intention to travel the indirect effect of destination image is significant.Keywords: Destination Image; Intention to Travel; Perceived Risk; Destination Attractiveness; Perceived Value